Simulation modeling of students' registration at MINDS - Nurul Farrah Dina, Abd Wahid (2011)
Simulation Modeling of Students'Registration at MINDS is a standalone system used by party that is responsible for lIMP student's registration which is Academic Management Division (BPA).Each year,the registration process which consists of several checkpoints that students need to go through in order to complete the registration process is always expected to be smooth,efficient and able be done in a short time.However,it is not always possible to fulfil these expectations as the procedures are meticulous and consumes a lot of time,cost and workforce on top of the increasing numbers of students every year.As for the responsible party (BPA),it is difficult for them in allocating counters or checkpoints involved' in the procedures that would give the optimal result of efficiency ahead of the operation.Thus, this system is developed as to propose a solution that will help the executor in decision making for the next registration by applying simulation modelling approach.The data collected are analysed and the proposed solution is chose based on the running of several scenarios that have been considered.